Effectiveness of Extract Supplements (Apium graveolens L.) to Estrogen Receptors Expression and Oocyte Diameter at Nucleolar Chromatin and Perinucleolar Stages in Female of Nile tilapia (Oreochromis niloticus L.) - Rikardo, Novy Kurnia; Marhendra, Agung Pramana Warih; Kurniawan, Nia; Riawan, Wibi; Rahayu, Sri (The Journal of Experimental Life Science, 2023)
The study of the use of celery (Apium graveolens L.) in the health sector has been widely discussed. The analysis of the use of celery in the process of oocyte development still needs to be addressed. This study was conducted to see the effect of celery extract on the expression of estrogen receptors on the gonads and oocyte diameter in tilapia for the first time. Fish are divided into four groups: P0 = Control treatment, feed without mixture; P1 = Treatment with celery extract concentration of 2,000 mg.kg-1 of feed; P2 = Treatment with celery extract concentration of 4,000 mg.kg-1 of feed; P3 = Treatment with celery extract concentration of 6,000 mg.kg-1 of feed. The results showed celery extracts expressed estrogen receptors on the gonads. The expressed estrogen receptor is the estrogen receptor β, whereas the estrogen receptor α is not detected in the gonad. Group statistical tests ANOVA showed no significant results in the development of oocytes. On the other hand, celery extract also impacted the development of oocytes at the nucleolar stage of chromatin, with a markedly greater oocyte diameter. Meanwhile, in the perinucleolar stage, celery extract reduces the oocyte diameter. Keywords: Apium graveolens L, ERα, ERβ, nucleolar chromatin, perinucleolar.